Various birth techniques: home birth, water birth, lotus birth, hypno birth, and birth position - Winata, I Gde Sastra; Harrista, Daniel Victor; Setiawan, William Alexander (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2024)
Background: The birth process varies greatly; health workers should be able to provide education about each technique and help patients plan their labor process. Each delivery technique is assessed from the mother's side and the baby's side, not only for patient satisfaction but also for patient safety. This article will provide a review of various birth technique known which are home birth, water birth, lotus birth, hypno birth, and including various birth position. Methods: This article is a systematic review of qualitative and quantitative studies from studies published in PubMed, Cochrane, the British Medical Journal, BioMed Central, and Elsevier, published in 2015 to 2023. The study sample included healthy maternal nulliparous or multiparous women with a low risk of complications. The focus of the research is on childbirth using home birth techniques, water birth, lotus birth, hypno birth, and birth positions. This article includes research conducted in hospitals, maternity homes, and patients' homes. Results: There are 6 studies included in this review. Each of which provide the perspectives and experiences of patients and healthworkers regarding various birth technique used. Conclusions: Each birthing technique has its own advantages and disadvantages. Each birthing technique also has its own recommendation criteria so that a birthing technique cannot be used for every birthing patient. The birthing technique and birthing position must be adjusted to the patient's condition and the medical facilities available at that time.